Chest CT Scan Findings in Symptomatic Patients Infected with COVID-19 in Norvic International Hospital, Nepal - Shahi, R. R.; Sapkota, M. R.; Budhathoki, L.; Manandhar, S.; Regmi, D. (Kathmandu University Medical Journal, 2021)
Background Coronavirus disease (COVID-19) is the recent global health emergency making it crucial for rapid diagnosis and intervention. Computed tomography (CT) is important for screening, diagnosis and evaluating severity and disease progress. Objective To assess the CT changes in COVID patients and study its relationship with various factors. Method A retrospective study was conducted at Norvic International hospital from August 2020 to November 2020 among RT-PCR positive symptomatic COVID cases who had positive CT changes. CT imaging data were analyzed by radiology expertise. Statistical analysis was carried out with the help of SPSS 16. Result Out of 120 patients, 75% were males and mean age was 54.70±15.56 years. The mean CT severity score was 18.35±6.87. Pure ground glass opacities was seen in 74(61.7%), reticulations 89(74.2%) and crazy-paving pattern 28(23.3%). CT scans with bilateral 118(98.3%) and peripheral involvement 109(90.8%) in all five lobes. CT- severity score was positively correlated with oxygen and mechanical ventilation requirement (P-value < 0.05 and 0.011 respectively). Conclusion CT findings including pure ground glass opacities, reticulations, bilateral and peripheral involvement involving all five lobes were more frequent. Our data suggest that CT-severity score significantly correlates with oxygen and mechanical ventilation requirements.